Bile duct injury after cholecystectomy: timing of surgical repair should be based on clinical presentation. The experience of a tertiary referral center with Hepp-Couinaud hepatico-jejunostomy - Giuliante, Felice; Panettieri, Elena; De Rose, Agostino M.; Murazio, Marino; Vellone, Maria; Mele, Caterina; Clemente, Gennaro; Giovannini, Ivo; Nuzzo, Gennaro; Ardito, Francesco (Updates in Surgery, 2023)
Impact of timing of repair on outcomes of patients repaired with Hepp-Couinaud hepatico-jejunostomy (HC-HJ) after bile duct injury (BDI) during cholecystectomy remains debated. This is an observational retrospective study at a tertiary referral hepato-biliary center. HC-HJ was always performed in patients without sepsis or bile leak and with dilated bile ducts. Timing of repair was classified as: early (≤ 2 weeks), intermediate (> 2 weeks, ≤ 6 weeks), and delayed (> 6 weeks). 114 patients underwent HC-HJ between 1994 and 2022: 42.1% underwent previous attempts of repair at referring institutions (Group A) and 57.9% were referred without any attempt of repair before referral (Group B). Overall, a delayed HC-HJ was performed in 78% of patients; intermediate and early repair were performed in 17% and 6%, respectively. In Group B, 10.6% of patients underwent an early, 27.3% an intermediate, and 62.1% a delayed repair. Postoperative mortality was nil. Median follow-up was 106.7 months. Overall primary patency (PP) attainment rate was 94.7%, with a 5- and 10-year actuarial primary patency (APP) of 84.6% and 84%, respectively. Post-repair bile leak was associated with PP loss in the entire population (odds ratio [OR] 9.75, 95% confidence interval [CI] 1.64–57.87, p = 0.012); no correlation of PP loss with timing of repair was noted. Treatment of anastomotic stricture (occurred in 15.3% of patients) was performed with percutaneous treatment, achieving absence of biliary symptoms in 93% and 91% of cases at 5 and 10 years, respectively. BDI can be successfully repaired by HC-HJ regardless of timing when surgery is performed in stable patients with dilated bile ducts and without bile leak.